Using Cash Flows to Predict Bankruptcy of Chemical Companies: Case Study Approach - Siow, Hui Wen (2009)
The intent of this study is to present an argument for the usefulness of cash flow information in bankruptcy prediction, and whether cash flow information provide a superior prediction of business failure over the conventional accrual accounting information. In addition, this dissertation also aim to analyze other important factors leading to bankruptcy, particularly contingent liabilities in which the obligations are not accrued and accounted for, nor are they considered in conventional bankruptcy assessment. Multiple case study approach is applied on three American chemical companies which had filed for bankruptcy in year 2003, i.e. Solutia Inc., Mississippi Chemical Corporation, and General Chemical Industrial Products Inc. Quantitative analysis is performed using cash flow ratios and conventional accrual base information covering nine to ten years data before bankruptcy, together with the industry and trend analysis. Qualitative analysis and discussion on contingent liabilities is presented on litigation and claim, as well as loan default and covenant violation, both being identified as having high bankruptcy risk in the chemical industry. The results show that cash flow information is effective in predicting corporate bankruptcy, particularly by using Cash Flow to Total Debt ratio, Operating Cash Flow ratio and Investing Cash Flow trend. The results from conventional accrual base bankruptcy model analysis show that it is able to predict business failure as effective as the cash flow information. However, there is risk of misclassifying non-bankrupt company as bankrupt company in the chemical industry, as ambiguous results are shown from the assessment of non-bankrupt companies.